PERTUMBUHAN DPK, PINJAMAN DITERIMA, PENEMPATAN PADA BANK LAIN, SURAT BERHARGA DAN KREDIT UNTUK PERTUMBUHAN EFISIENSI PADA BANK PEMERINTAH DAERAH - Anggraeni . (STIE Perbanas Surabaya, 2013)
The bank is a financial institution that serves as an intermediary for those who have surplus funds to those who need it. Beside, banking activities include funding, lending and providing other services. In addition, funding activities include demand deposits, saving deposits and time deposits. While lending activities interbank placement, commercial papers and credits. To obtain profits, the bank needs to measure its ability to conduct its operations, one of which it uses the ratio of the efficiency ratio of operating expenses to operating income. The study uses sample of Regional Government Bank during the period 2010-2012 with total assets of over 10 trillion. There are six bank used as a sample, namely PT. BPD. Kalimantan Timur, PT. BPD. Riau, PT. BPD. Jawa Tengah, PT. BPD. Jawa Timur, PT. BPD Sumatra Utara. Based on this research, the growth of demand deposits, saving deposits, time deposit, loan received, inter- bank placement, commercial papers, and credit simultaneously have a significant effect on the growth of BOPO, by 28 %. Among the seven independent variables, there are three independ- ent variables that have a significant influence on the dependent such as time deposit growth with 9.92 %, the growth loan by 5.24 %, the growth interbank placement by 9.30%.